Educação midiática : uma proposta para a escola - Roznieski, Raíza Ismério (2022)
Among the skills desired for students to understand the contemporary context, the National Common Curricular Base in Brazil points to Media Literacy. Quality information is essential for the construction of critical and useful knowledge for actually solving problems, especially for the construction of studies on their way. In addition, the understanding of this context will also contribute to Media Literacy, guiding them through a safe use of the internet, making them aware of frauds and scams and how to avoid it, while preventing both mental and material losses. However, Media Literacy at National Common Curricular Base is only contemplated for students starting at year 5 (x-year-old and above), leaving younger children from Earlier Education helpless in this learning process. It is also understood that teachers are the transforming agents of this story. Therefore, the present investigation aims at the introduction of Media Literacy in the context of Early Childhood Education and Elementary School I, through a document analysis that investigated the national and international scenarios, through State of the Art methodology. Subsequently, the analysis of available resources was carried out, identifying the absence of materials for teachers to work with Media Literacy in Early Childhood Education and the first half of Elementary School. In light of this finding, we developed a Teacher's Guide, composed of pedagogical practices in Media Literacy, a free e-book and suggestions for evaluation criteria. It is expected that, as the new generations come forward, they will have opportunities to develop critical sense and become more active citizens.